Real time signal processing techniques in a dual beam sonar system for fish stock assessment - MITCHELL, R. S.; STEPNOWSKI, A.; DROBNIK, J.; GREEN, D. R. (Archives of Acoustics, 1988)
Advances in VLSI technology including A/D converters, large high speed memories and digital signal processing devices, combined with a dramatic improvement in high performance single board computer SBCs, have radically altered design possibilities for sonar systems [1, 2]. It is now possible to centralize the system functions in one controller and transfer much of the signal processing from hardware to software. Furthermore, digital signal processing techniques may be employed to improve the system's performance and reliability. In this paper, we describe a new stock assessment dual beam sonar designed to take advantage of modern computer architectures and digital signal processing techniques. We also discuss some original processing enhancements to the basic dual beam concept both in hardware and software which have been built into the sonar system. The system is flexible so that the same hardware is employed for various modes. The transfer of functions from hardware to software combined with a hihgly efficient transmitter has yielded a low cost compact system.